IMPLEMENTASI LESSON STUDY UNTUK MENINGKATKAN PELAKSANAAN PENDEKATAN SCIENTIFIC GURU KIMIA DI MADRASAH ALIYAH AL-FATAH DAN MADRASAH ALIYAH NEGERI 2 PALEMBANG - Muhammad Isnaini; Wiwid P Ningrum (Chemistry Education Department of Education and Teaching Faculty, 2019)
The aim of Implementation of lesson study in community service are to improve the quality of teaching and learning using scientific approach. Data sources from 25 teachers of Mathematics and Natural Sciences (chemistry, biology, physics). The implementation is carried out in two cycles, each cycle consisting of the stages of plan, do, and see with the application of learning in the subjects of hydrocarbon chemistry in class XI and chemical bonds in class X. Data collection techniques used are observation with observation sheet instruments and documentation containing photos and videos. Data were analyzed descriptively. Implementation results prove how scientific learning in subjects can improve the quality of learning in chemistry subjects. In class students become more active, learning becomes more conducive, group discussion becomes more lively because all of group members prepare the discussion materials correctly. They are become more enthusiastic and active. In addition, teachers can collaborate, share knowledge and can improve teacher competency and the quality of learning.